2021
DOI: 10.12968/jowc.2021.30.sup9a.iii
|View full text |Cite
|
Sign up to set email alerts
|

Microcurrent stimulates cell proliferation and modulates cytokine release in fibroblast cells

Abstract: Aims: To analyse the effects of microcurrent on L929 fibroblast cell culture. Methods: Cells were cultivated in six-well plates at densities of 5×104, 1×105, 3×105 and 5×105 cells/well to determine the best plating density. Subsequently, two methods of current application were tested: with a paper cone coupled to the electrode (M1) and with the electrode directly inside the well (M2). Then, streams of 60µA (G60), 100µA (G100), 500µA (G500) and 900µA (G900) were applied to the cells (n=3) once a day for three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Notably, to the best of our knowledge, this is the first report on the impact of a weak constant direct electrical current on the transcriptional regulation of cardiac myofibroblasts, expanding the current understanding of electrical stimulation in cardiology. To date, electrical stimulation studies on cardiology have focused on fibroblast cell migration in the context of wound healing or conductive biomaterials to promote CM maturation and reprogramming, or muscle contractions, overlooking its impact on myofibroblasts [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, to the best of our knowledge, this is the first report on the impact of a weak constant direct electrical current on the transcriptional regulation of cardiac myofibroblasts, expanding the current understanding of electrical stimulation in cardiology. To date, electrical stimulation studies on cardiology have focused on fibroblast cell migration in the context of wound healing or conductive biomaterials to promote CM maturation and reprogramming, or muscle contractions, overlooking its impact on myofibroblasts [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation can have diverse effects on cells, such as facilitating myofibroblast differentiation for wound healing [ 34 , 35 , 36 ] or increasing cell proliferation and altering ECM components [ 20 , 36 , 37 ]. The different outcomes can be attributed to several factors, such as differences in the cell types studied and the current form.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other ES methods that can bypass cells, this form of MC can exert effects directly on cells [ 19 ] and may even be more effective in stimulating cell physiology and growth [ 20 ]. A recent in vitro study by Bravo et al [ 21 ] demonstrated that MC plays a crucial role in wound healing by increasing fibroblast cell proliferation, modulating the inflammatory response, and aiding tissue regeneration compared to controls. In addition, a novel “Microcurrent Dressing” that uses MC on moist wound surfaces to accelerate wound healing has been investigated and the clinical effectiveness has been verified [ 22 ].…”
Section: Introductionmentioning
confidence: 99%